The Relationship of Parent Support with Children's Learning Motivation School Age in Study from Home (SFH) Method During Covid-19 Pandemic - Maya Wulandari; Tri Sakti Widyaningsih; Wahyuningsih Wahyuningsih (Indonesian Journal of Global Health Research, 2022)
This study is to identify the relationship between parental support and learning motivation for school-age children in the study from home (SFH) method during the COVID- 19 pandemic in Trisobo Village, Boja District, Kendal City. This study aims to look at parental support with school-age children's learning motivation, as well as the relationship between the two variables. This type of research is a type of quantitative research. The population of this research is elementary school students in Trisobo Village who carry out learning from home aged 6-12 years. Sampling technique with stratified random sampling was taken as much as 60% of the population, namely 47 people, data collection techniques using questionnaires, data collection tools using questionnaires, and data analysis using frequency distribution. The results showed that; (1) parental support is categorized as low; (2) children's learning motivation is still low; (3) there is a significant relationship between parental support and learning motivation. (1) Parental support in Trisobo Village has low parental support of 4 respondents (8.5%), moderate parental support of 29 respondents (61.7%) and high parental support of 14 respondents (29 ,8%); (2) learning motivation of school-age children in Trisobo Village has low learning motivation as many as 5 respondents (10.6%), moderate learning motivation as many as 27 respondents (57.4%) and high learning motivation as many as 15 respondents (31.9%) ; (3) the coefficient value or r value = 0.533 indicates moderate closeness in a positive direction, which means the higher parental support, the higher the learning motivation of school-age children in the Study From Home (SFH) method during the covid-19 pandemic.